La narrativa visual en la promoción y reconocimiento de los grupos de danza folklórica en la ciudad de Ambato. - Guamán López, Danny Ariel (2024)
This research project is carried out after evidencing the scarce use of advertising tools within the folkloric dance groups in the city of Ambato. Thus, basic tools were proposed within the graphic design that can be of support for the different groups to carry their advertising management and graphic identity in a coherent way connecting with the public in a more professional manner. Thus, based on the inductive method, theories already established by experts for the knowledge of visual narrative were reviewed, as well as the use of specific collection techniques to know the management of advertising pieces within these dance groups and thus understand if a correct or incorrect use of the different elements present in these visual compositions is made. To meet these objectives we had the help of various dance groups who told us their way of perceiving advertising from the cultural field, as well as the help of experts in graphic design to raise the proposal for the benefit of folkloric dance groups. This project has the purpose of contributing in a positive way to the Ecuadorian folkloric dance groups in the city of Ambato with the purpose of making use of the different techniques present in this project to improve the visualization of these groups in a graphic way through the use of visual narrative and its diversities